Reduction of minerals in feedlot diets of Nellore cattle: impacts on intake, performance, and nutrient requirements; and prediction of chemical rib section composition by dual energy x-ray absorptiometry in Zebu cattle - Prados, Laura Franco (2016)
The present work was developed based on three studies. The objective of the first study was to evaluate a method to predict the 9th to 11th rib section (rib9-11) composition through empirical equations using Dual Energy X-ray Absorptiometry (DXA). DXA is a validated method used to describe tissue composition in humans and other animals, but few studies have evaluated this technique in beef cattle, and especially in the Zebu genotype. A total of 116 rib9-11 sections were used to evaluate published prediction equations for rib9-11 composition and to develop new regression models using a cross-validation procedure. For the proposed models, 93 ribs were randomly selected to calculate the new regression equations, and 23 different ribs were randomly selected to validate the regressions. The rib9-11 sections from left carcasses were taken from Nellore and Nellore × Angus bulls from three different studies and scanned using DXA equipment (GE Healthcare, Madison, Wisconsin, USA) in the Health Division at Universidade Federal de Viçosa. The outputs of the DXA report were DXA lean (g), DXA fat free mass (g), DXA fat mass (g), and DXA BMC (bone mineral content; g). After being scanned, the rib9-11 sections were dissected, grounded, and chemically analyzed for total EE, CP, water, and ash content. The predictions of rib fat and protein from previous published equations were different (P < 0.01) from the observed composition. New equations were established through leave-one-out cross-validation using REG procedure using SAS. The equations were as follows: Lean (g) = 37.082 + 0.907× DXA lean (R 2 = 0.95); Fat free mass (g) = 103.224 + 0.869 × DXA fat free mass (R2 = 0.93); EE mass (g) = 122.404 + 1.119 × DXA fat mass (R2 = 0.86); Ash mass (g) = 18.722 + 1.016 × DXA BMC (R2 = 0.39). The equations were validated using Mayer’s test, the concordance correlation coefficient (CCC), and the mean square error of prediction (MSEP) for decomposition. Comparing observed and predicted values using the new equations, Mayer’s test was not significant for lean mass (P = 0.26), fat free mass (P = 0.67), EE mass (P = 0.054), and ash mass (P = 0.14). We concluded that the rib9-11 composition of Nellore and Nellore × Angus bulls can be estimated from DXA using the proposed equations. The second study was developed using weaned Nellore bulls (n = 36; 274 ± 34 kg) in a randomized complete block 2 × 2 factorial design experiment to evaluate intake, fecal excretion and performance with different levels of minerals. The design included two levels of Ca and P (macro mineral factor; CaP+ or CaP-) and two levels of micro minerals (micro mineral factor; ZnMnCu+ or ZnMnCu-). The factor CaP- was without supplementation of limestone and dicalcium phosphate and the factor ZnMnCu- was without inorganic supplementation of micro minerals. The diets were isonitrogenous (13.3% CP). Intake was individually monitored every day. Indigestible NDF was used as an internal marker for fecal excretion measurements. The animals were slaughtered (84 and 147 days on feed; DOF), carcass characteristics were measured and liver and rib samples were collected. Feed, feces, rib bones and liver samples were analyzed for DM, ash, CP, EE, Ca, P, and micro minerals (Zn, Mn, and Cu). There were no significant interactions (P ≥ 0.06) between macro and micro minerals supplementation for any variables in the study. Calcium, P and micro minerals concentrations did not affect (P ≥ 0.20) intakes of DM, OM, NDF, EE, CP, TDN and NFC. Calcium and P intake were affected (P < 0.01) by macro mineral factor. Animals fed without Ca and P supplementation consumed lower levels of these minerals. Dry matter and nutrient fecal excretion were similar (P ≥ 0.23) among factors. Performance and carcass characteristics were similar (P ≥ 0.09) among diets. The content of ash in rib bones was not affected (P ≥ 0.06) by diets. Phosphorus and phosphatase alkaline plasma concentration were similar (P ≥ 0.52) among diets. Calcium plasma concentration was affected (P < 0.01) by micro mineral factor; nevertheless, all blood metabolites were within the reference values. Fecal excretion of Ca and P was different (P < 0.01) among macro mineral factor. These results indicate that supplementation of minerals (Ca, P, Zn, Mn, and Cu) is not necessary in conventional feedlot diets for finishing Nellore. Dietary reductions in these minerals would represent a decrease in the costs of feedlot diets. Dietary reductions in Ca and P decrease fecal excretion of these minerals. Decreasing the P fecal excretion through decreasing content minerals is an opportunity to reduce environmental impact of feedlot operations. The third study aimed to evaluate the water intake, the chemical body composition, the residual feed intake and gain, and the nutritional requirements of energy, protein for maintenance and gain, and calcium and phosphorus for maintenance of Nellore bulls, as well as their efficiencies. Weaned Nellore bulls (n = 44; 273 ± 34 kg) were fed in a randomized complete block design 2 × 2 factorial arrangement to evaluate the nutritional requirements with absence or presence of mineral supplementation. The design included two levels of Ca and P (macro mineral factor; CaP+ or CaP-) and two levels of micro minerals (micro mineral factor; ZnMnCu+ or ZnMnCu-). The diets were isonitrogenous (13.3% CP). Intake was individually monitored every day. Indigestible NDF was used as an internal marker for digestibility measurements. Four animals were used in the reference group (harvested d 0); four bulls were fed at the maintenance level (1.1% of BW); and the remaining 36 bulls were fed ad libitum. Bulls are blocked by days on fed, they were slaughtered on d 84 and 147, after slaughter, samples of the whole body were taken. All samples were lyophilized, ground with liquid nitrogen and grouped as percentage of component in empty BW from each bull. Samples were analyzed for DM, ash, CP, EE, Ca, and P. The water intake was similar (P ≥ 0.07) among treatments. The average of free water intake was 17 L/d for each bull. High residual feed intake and gain (RFIG) bulls had lower DMI (P < 0.01) than low RFIG bulls, but similar ADG (P = 0.82). The CP, EE and water present in the EBW increased as the animal grew, the ash growth is lower than the EBW. Non-linear regression equations were developed to predict heat production (HP) from metabolizable energy (ME) intake and retained energy (RE). The net energy requirements for maintenance (NEm) and metabolizable energy for maintenance (MEm) were 66.5 and 107 kcal/EBW0.75/d, respectively. The efficiency (km) was 62%. The equation obtained for net energy for gain (NEg) was: NEg (Mcal/day) = 0.0388 × EBW0.75 × EBWG1.095 and the efficiency was 25%. For net protein for gain was: NPg (g/day) = 179.74 × EBWG – 5.43 × RE. The net maintenance requirement for Ca was 2.33 mg/EBW and for P was 9.10 mg/EBW. The coefficient of absorption for Ca was 54% and P was 64%. In conclusion, the requirement of net energy for maintenance for Nellore feedlot cattle is 66.5 kcal/EBW0.75/day. Requirements of net energy for gain and net protein for gain can be obtained by the following equations: NEg (Mcal/day) = 0.0388 × EBW0.75 × EBWG1.095 and NPg (g/day) = 179.74 × EBWG – 5.43 × RE. Net maintenance requirement for Ca is 2.33 mg/EBW and for P is 9.10 mg/EBW. The coefficient of absorption for Ca is 54% and P is 64%. The water intake is not influenced by supplementation of Ca, P, Zn, Mn, and Cu. High residual feed intake and gain bulls has lower DMI than low RFIG bulls, with similar ADG. The CP, EE and water present in the EBW increased as the animal grew, the ash growth is lower than the EBW. Overall, intake and performance was not affect by minerals (Ca, P, Zn, Mn, and Cu) diet reduction. It was concluded that the reduction of minerals contents in feedlot diets for Nellore finishing bulls appears not influence in intake, performance, chemical body composition, and nutrient requirements of Nellore finishing bulls in feedlot.